Visual Basic 2005 cookbook - Craig, John Clark (O'Reilly Media, 2006)
This book will help you solve more than 300 of the most common and not-so-common tasks that working Visual Basic 2005 programmers face every day. If you're a seasoned .NET developer, beginning Visual Basic programmer, or a developer seeking a simple and clear migration path from VB6 to Visual Basic 2005, the Visual Basic 2005 Cookbook delivers a practical collection of problem-solving recipes for a broad range of Visual Basic programming tasks. The concise solutions and examples in the Visual Basic 2005 Cookbook range from simple tasks to the more complex, organized by the types of problems you need to solve. Nearly every recipe contains a complete, documented code sample showing you how to solve the specific problem, as well as a discussion of how the underlying technology works and that outlines alternatives, limitations, and other considerations. As with all O'Reilly Cookbooks, each recipe helps you quickly understand a problem, learn how to solve it, and anticipate potential tradeoffs or ramifications. Useful features of the book include: Over 300 recipes written in the familiar O'Reilly Problem-Solution-Discussion format Hundreds of code snippets, examples, and complete solutions available for download VB6 updates to alert VB6 programmers to code-breaking changes in Visual Basic 2005 Recipes that target Visual Basic 2005 features not included in previous releases Code examples covering everyday data manipulation techniques and language fundamentals Advanced projects focusing on multimedia and mathematical transformations using linear algebraic methods Specialized topics covering files and file systems, printing, and databases In addition, you'll find chapters on cryptography and compression, graphics, and special programming techniques. Whether you're a beginner or an expert, the Visual Basic 2005 Cookbook is sure to save you time, serving up the code you need, when you need it.